Inverse Design of Centrifugal Compressor Stages Using a Meanline Approach - Yuri Biba; Peter Menegay (International Journal of Rotating Machinery)
This article discusses an approach for determining meanline geometric parameters of centrifugal compressor stages given specified performance requirements. This is commonly known as the inverse design approach. The opposite process, that of calculating performance parameters based on geometry input is usually called analysis, or direct calculation. An algorithm and computer code implementing the inverse approach is described. As an alternative to commercially available inverse design codes, this tool is intended for exclusive OEM use and calls a trusted database of loss models for individual stage components, such as impellers, guide vanes, diffusers, etc. The algorithm extends applicability of the inverse design code by ensuring energy conservation for any working medium, like imperfect gases. The concept of loss coefficient for rotating impellers is introduced for improved loss modelling. The governing conservation equations for each component of a stage are presented, and then described in terms of an iterative procedure which calculates the required one-dimensional geometry. A graphical user interface which facilitates user input and presentation of results is discussed briefly. The object-oriented nature of the code is highlighted as a platform which easily provides for maintainability and future extensions.